Analysis of linoleoyl and oleoyl macrogolglycerides by high performance liquid chromatography coupled to the atmospheric pressure photoionization mass spectrometry - Kemel Kamilia; Libong Danielle; Solgadi Audrey; Tfaili Sana; Baillet-Guffroy Arlette; Laugel Cécile (Oilseeds and fats, crops and lipids, 2020)
Linoleoyl macrogolglyceride (LM) and oleoyl macrogolglyceride (OM) are pharmaceutical ingredients, obtained from corn and apricot kernel oils respectively. This study aims to know the detailed chemical composition of LM and OM, in order to understand their roles in pharmaceutical formulations. These two products were analyzed by non-aqueous reversed phase high-performance liquid chromatography (NARP-HPLC), using Vintage Series KR C18 column (250 × 4.6 mm, 5 µm) and non-aqueous acetonitrile/acetone mixture as mobile phase. The ionization source used was atmospheric pressure photoionization (APPI) and the analyzer was LTQ-Orbitrap® (hybrid analyzer: double linear ion trap coupled to a Fourier transform orbital trap). LM and OM consist of complex mixtures, constituted of mono-(MG), di-(DG) and triglycerides (TG) and mono-(MPEGE) and di PEG-6 esters (DPEGE) of linoleic acid (18:2) for LM and of oleic acid (18:1) for OM. NARP-HPLC-APPI method allowed the separation and the identification of the glyceride classes (MGs, DGs and TGs) and the PEG esters of different chain lengths (PEG-chain lengths of fatty acid moieties and number of units of ethylene oxide), at the same time and in one single run, for both products LM and OM. The comparative study between LM and OM showed that, a higher presence of linoleic esters for LM, and a higher presence of oleic esters for OM.